Developing Vocabulary Material Using Game Quiz Vocabulary in Teaching Speaking - Jumiati, Trie; Supartini, Nai (Journal of Linguistics, Literacy, and Pedagogy, 2024)
The goals of this study are to define the procedure and outcomes of creating the vocabulary material using game quiz vocabulary in speaking instruction, to characterize the viability of creating vocabulary materials using game quiz vocabulary in speaking instruction based on the opinions of experts and practitioners, and to analyze the responses of teachers and students to the learning modules. There were three groups of the subject for this study: the students, the researcher as an observer and the English teacher in the class. The first validator provided the score of 84%. Likewise, the product received additional 80% of the total score from the second validator. The both validators concluded that the developmental product was adequate for teaching students how to speak. The vocabulary suitability procedure for the game quiz is broken down into two sections: an initial restricted field test and a main field test. According to the initial validation data, the developmental product obtained an 89% accumulation score. However, the second validation result received an 84% score increase. In addition, during the most recent meeting, the researcher asked the observer to assess the developmental product.